Developing a Principled Framework for Materials Development - Nurul Azizah (Universitas Muhammadiyah Makassar, 2026)
This study explored the development of a principled framework for language materials development in order to align instructional resources with curriculum objectives, pedagogical principles, and learners’ needs. The problem addressed in this study was the lack of systematic guidance in designing materials that are not only linguistically accurate but also contextually relevant, engaging, and inclusive. A qualitative descriptive approach was employed using document analysis of relevant literature and curriculum policy documents. The data were obtained from books, journal articles, and official guidelines related to materials development, educational theories, and the Merdeka Curriculum. The data were analyzed through thematic analysis by identifying and synthesizing key principles such as authenticity, learner engagement, scaffolding, formative assessment, cultural relevance, and technology integration. The findings indicated that a principled framework played a significant role in ensuring the effectiveness and coherence of teaching materials. The integration of theoretical foundations with curriculum requirements resulted in materials that supported learner autonomy, critical thinking, and meaningful language use. Furthermore, the study highlighted the importance of inclusivity and adaptability in diverse educational contexts. In conclusion, the developed framework provided practical guidance for educators and material developers to design effective, learner-centered, and contextually appropriate materials.